Le cas francais de I'Observatoire des territoires. L'evidence par la prospective ou par l'observation? - Bovar, Odile; Peyrony, Jean (TH Zürich, NSL, 2006)
Der Beitrag präsentiert die Länderstudie Frankreich zum Thema der wissensbasierten Planung. Er beschreibt die Aufgaben und die Organisation der Raumbeobachtung durch DIACT, einer ressortübergreifenden Einrichtung, die raumbezogene Informationen erhebt und den Akteuren in der Politik zur Verfügung stellt. Der Beitrag begründet die Notwendigkeit einer Beteiligung der Bürger an den raumbezogenen Planungsprozessen. goj/difu

In the field of "evidence-based planning", this paper presents the French case. In France, strategic planning may be seen as a compromise between "industrial" values (illustrated by Saint Simon) and "civic" values. DATAR was created to develop a spatial planning policy, whose "evidence" has been primarily based on catastrophic prospective scenarios. The explicit function of observation appeared more recently in the context of European construction and decentralization. The paper presents the organisation (Council, network, technical team, Web site) and methodology (shared diag noses, scientific advice) that allows the French "territorial observatory" to be a tool for piloting spatial planning policies. The paper concludes with the necessity to involve citizens in the process either through a prospective viewpoint or through observation, in order to make them "believe what they know." difu
Keywords: Raumordnung; Raumplanung; Planungstheorie; Raumordnungspolitik; Planungspraxis; Planungsmethode; Bürgerbeteiligung; Raumbeobachtung; Planungswissenschaft